Silent Electromechanical Car Sensor - Thoren, Claes; Klemets, Linus (My University, 2011)
A prototype of an integrated electronics car sensor has been developed. It is a device that locks a vehicle seat belt when it is tilted or horizontally accelerated more than normally expected for a vehicle, keeping the occupant safely in her seat. It uses an accelerometer as sensor, an FPGA for signal processing and a truck belt retractor containing an electromechanical actuator. A comparison between a mechanical car sensor and the prototype car sensor show that it is possible to get comparable performance and a more silent operation using the prototype. Further it is possible to automatically calibrate the prototype car sensor so that the sensor might be installed with an inclination relative to the horizontal plane, enabling development cost cutting being able to use a belt retractor model for several car models. A drawback is that this car sensor demands a power supply.
Keywords: Elektroteknik och elektronik; Produktion; Transport; Electrical Engineering, Electronic Engineering, Information Engineering; Production; Transport